Compensating Image Distortions in a Commercial Reflectron-Type Atom Probe - Heller, Martina; Ott, Benedict; Felfer, Peter (Microscopy and Microanalysis, 2024)
In atom probe tomography, the spatial resolution and accuracy of the data critically depend on the 3D reconstruction of the 2D detector data. Atom probes with a reflectron have an improved mass resolving power and must include a model of the imaging properties of the reflectron. However, for modern wide-angle reflectron instruments, these imaging properties are not trivial and need to be determined for the reflectron used. This is typically done by the instrument manufacturer, and due to the proprietary nature of the instrument design, the imaging properties are opaque to the user. In this paper, we provide a method to determine the imaging properties of a reflectron that can easily be carried out on commercial instrumentation. This method is used to provide the user with a transformation function from the provided detector data, which can already contain some corrections applied, to a virtual detector placed before the reflectron. From there on, 3D reconstructions can be carried out analogous to straight flight path instruments. Correction algorithms and reference data for Imago/CAMECA LEAP 3000, 4000, 5000, and 6000 series instruments are also provided.
CRIS-Team Scopus Importer:2025-04-01
Keywords: APT data correction; atom probe; reflectron